Effect of butanol and terpinol as a solvents in GNP/SA conductive ink - Salim, Mohd Azli; Jori, Syamsul Hilmi; Masripan, Nor Azmmi; Md. Saad, Adzni; Photong, Chonlatee (Semarak Ilmu Publishing, 2024)
Silver hybrid inks have garnered significant attention in the realm of flexible electronics due to their remarkable conductivity and compatibility with various substrates. The selection of solvent profoundly influences the ink's properties and performance, encompassing SEM characteristics and electrical conductivity. This paper undertakes a comparative analysis of silver hybrid inks formulated with two distinct solvents: butanol and terpinol. The study delves into how the choice of solvent impacts pigment distribution within the ink and subsequently affects its electrical conductivity.